Development of high-power VCSEL emitter of size 30mm x 30mm, scalable in two dimensions and applicable to Si wafer annealing. (1st November 2022) - Noh, Youngsu; Park, Seungho; Kim, Byung-Kuk; Park, Wang-Jun; Kim, Taehyung; Kim, Hyoung June
Highlights: 30 mm × 30 mm square VCSEL emitter of 47 . 6 W / c m 2 optical power density. Two-dimensionally scalable and applicable to large area targets. Microchannel water cooling block for thermal management of each VCSEL emitter. Mode and divergence of a single beam emitted from a VCSEL diode of 30 μ m . Thermal annealing of 4" Si wafers by using a module of 9 VCSEL emitters. Abstract: Two-dimensionally scalable vertical cavity surface emitting laser (VCSEL) emitter of size 30 mm × 30 mm was designed and fabricated for practical applications in the rapid heating processes of large-area targets. Nine emitters were arranged in a 3 × 3 array for an experimental VCSEL module, which was used for annealing of a 4" Si wafer. Each emitter was composed of 120 chips of size 1 . 26 mm × 1.26 mm, and each chip was composed of 770 VCSEL diodes of 30 μ m in diameter, emitting a continuous beam with wavelength of 940 nm and maximum optical power density of 47 . 6 W / c m 2 . Since VCSELs generated a significant amount of Joule heat during operation, an effective cooling system was required for reliable thermal management of the emitter. A water cooling block of 126 microchannel flow passages with the heat transfer area-to-volume ratio approximately 1270 m 2 / m 3 was designed and fabricated for each emitter, resulting in the thermal resistance of 0 . 012 K / W, equivalent to the overall heat transfer coefficient of 92, 000 W / m 2 K at water flow rate of 1 L / min, which was the minimum value for the normal operation of the emitter. By comparing the experimental images on the 4" Si wafer irradiated by the single emitter and by the module with the numerical predictions based on the ray-tracing method, the laser beam emitted from a single VCSEL diode of 30 μ m in diameter was estimated to have the mode of TEM01* (doughnut profile, multimode) and a divergence angle of 20 ∘ . These were two factors that affected the irradiation uniformity on the target. In addition, to validate the applicability of the high-power VCSEL system to anneal large-area targets, the heating process of 4" Si wafers using the module of nine emitters was experimentally carried out at atmospheric pressure, and was compared with numerical predictions. Graphical abstract: Image, graphical abstract